2007
DOI: 10.3844/ajassp.2007.397.404
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Pulsatile Blood Flow in a Stented Human Coronary Artery with a Flow Divider

Abstract: Shear stress is known to play a central role in restenosis formation and is sensitive to stent geometry. Local flow alterations created by a different stents without and with flow divider were studied to compare the hemodynamic effects of Stent design properties on restenosis in stented human coronary artery. Blood pressure and shear stress values were computed in three different sites, including stented arterial segment, pre-stent and post-stent regions using computational fluid dynamics. Blood flow was assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…where, The outflow boundary conditions were assumed to be zero pressure at the flow outlet and no slip conditions at the vessel wall. The dynamic viscosity of blood and its density were assumed to be 3.5×10 -3 Pa.s and 1050 kg/m 3 , respectively [19,20,21,22] . The blood velocity boundary conditions were obtained from phase contrast MRI scanning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where, The outflow boundary conditions were assumed to be zero pressure at the flow outlet and no slip conditions at the vessel wall. The dynamic viscosity of blood and its density were assumed to be 3.5×10 -3 Pa.s and 1050 kg/m 3 , respectively [19,20,21,22] . The blood velocity boundary conditions were obtained from phase contrast MRI scanning.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is difficult to verify conclusively such relationships without suitable in vivo studies, CFD can provide an excellent research tool to help understand these underlying issues. CFD is being employed by several researchers to explore further the nature of flow stagnation patterns on stent strut shape and spacing [20,21,22,23,24] . These studies have confirmed that the flow stagnation patterns between stent struts depend most strongly on stent strut spacing and have demonstrated that vessel wall compliance has little effect on these flow patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is a vascular disease that reduces arterial lumen size through plaque formation and arterial wall thickening. The pathological complications of atherosclerosis, namely Coronary Heart Disease (CHD) and stroke, remain the leading cause of mortality in the western world (Dehlaghi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of relationships between geometric variables and hemodynamic patterns can be used to infer which mechanical factors are more likely to be involved in the localization of disease (Dehlaghi et al, 2007;2008a;2008b;Wellnhofer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%